Dampak Beban Kendaraan Terhadap Umur Rencana Jalan dengan Metode Bina Marga 2017 - Angelina Mita Lorenza Sitorus; Ibnu Sholichin; Fithri Estikhamah (Institut Teknologi Garut, 2026)
The quality of road infrastructure is highly dependent on appropriate pavement design. This study analyzes the impact of vehicle loads on the pavement design life of the Driyorejo–Legundi road section. Based on the 2017 Bina Marga method, traffic data were collected over three days to estimate the road service life. It is projected that by 2025, the Average Daily Traffic will reach 23,213 vehicles per day. The calculation results indicate that due to excessive vehicle loads, the remaining service life of the road decreases by 3.89%, from 10 years to approximately 7.008 years. These findings confirm that overloading significantly reduces pavement service life, highlighting the need for serious attention during the planning and maintenance phases of road infrastructure. The study is expected to serve as a strong basis for sustainable-oriented road planning and to provide meaningful support for policies on controlling vehicle overloading in Indonesia.